Chemokine receptor–targeted PET/CT provides superior diagnostic performance in newly diagnosed marginal zone lymphoma patients: a head-to-head comparison with [18F]FDG - Kosmala, Aleksander; Duell, Johannes; Schneid, Simone; Serfling, Sebastian E.; Higuchi, Takahiro; Weich, Alexander; Lapa, Constantin; Hartrampf, Philipp E.; Raderer, Markus; Einsele, Hermann; Buck, Andreas K.; Topp, Max S.; et al. (European journal of nuclear medicine and molecular imaging, 2024)
Background In patients with marginal zone lymphoma (MZL), [ 18 F]FDG PET/CT provided inconsistent diagnostic accuracy. C-X-C motif chemokine receptor 4 (CXCR4) is overexpressed in MZL and thus, may emerge as novel theranostic target. We aimed to evaluate the diagnostic performance of CXCR4-targeting [ 68 Ga]Ga-PentixaFor when compared to [ 18 F]FDG PET/CT in MZL. Methods Thirty-two untreated MZL patients (nodal, n = 17; extranodal, n = 13; splenic, n = 2) received [ 68 Ga]Ga-PentixaFor and [ 18 F]FDG PET/CT within median 2 days. We performed a visual and quantitative analysis of the total lymphoma volume by measuring maximum/peak standardized uptake values (SUV max/peak ), and calculating target-to-background ratios (TBR, defined as lesion-based SUV peak divided by SUV mean from blood pool). Visual comparisons for both radiotracers were carried out for all target lesions (TL), and quantitative analysis of concordant TL evident on both scans. Last, MZL subtype analyses were also conducted. Results On a patient-based level, [ 68 Ga]Ga-PentixaFor identified MZL manifestations in 32 (100%) subjects (vs. [ 18 F]FDG, 25/32 [78.1%]). Of the 256 identified TL, 127/256 (49.6%) manifestations were evident only on CXCR4-directed imaging, while only 7/256 (2.7%) were identified on [ 18 F]FDG but missed by [ 68 Ga]Ga-PentixaFor. In the remaining 122/256 (47.7%) concordant TL, [ 68 Ga]Ga-PentixaFor consistently provided increased metrics when compared to [ 18 F]FDG: SUV max , 10.3 (range, 2.53–37.2) vs. 5.72 (2.32–37.0); SUV peak , 6.23 (1.58–25.7) vs. 3.87 (1.54–27.7); P < 0.01, respectively. Concordant TL TBR on [ 68 Ga]Ga-PentixaFor (median, 3.85; range, 1.05–16.0) was also approximately 1.8-fold higher relative to [ 18 F]FDG (median, 2.08; range, 0.81–28.8; P < 0.01). Those findings on image contrast, however, were driven by nodal MZL ( P < 0.01), and just missed significance for extranodal MZL ( P = 0.06). Conclusions In newly diagnosed MZL patients, [ 68 Ga]Ga-PentixaFor identified more sites of disease when compared to [ 18 F]FDG, irrespective of MZL subtype. Quantitative PET parameters including TBR were also higher on [ 68 Ga]Ga-PentixaFor PET/CT, suggesting improved diagnostic read-out using chemokine receptor-targeted imaging.